Hydroxychloroquine's false hope: How an obscure drug became a coronavirus 'cure' - Samuels, Elyse; Tancharoen, Maurissa; Seley-Radtke, Katherine; Donovan, Joan; Boulware, David (Washington Post, 2020)
Claims about hydroxychloroquine and chloroquine have taken hold of the global consciousness. Online conversations, media articles and politicians’ statements quickly - and incorrectly - labeled it as a ‘cure’ for covid-19, the disease caused by the novel coronavirus. Conversation around the drugs first spiked in mid-February after a Chinese news outlet tweeted about studies on the drugs. Word of the potential cure spread around the globe, reaching the U.S. in mid - March. A series of posts online, including a tweet by a blockchain investor, Elon Musk and President Trump, helped the idea gain traction. Trump has repeatedly championed hope in the drugs online and at press conferences. Yet scientists say there is only anecdotal evidence the drugs work to treat covid-19. Experts warn of lasting and dangerous consequences from promoting a drug with such a lack of scientific data it works. Already, a run on the drugs has caused a shortage for those who need it, like lupus and rheumatoid arthritis patients. The Fact Checker breaks down the data that shows when and how people began talking about hydroxychloroquine and chloroquine online - and highlights the fallout of overhyping drugs without concrete evidence
Hydroxychloroquine's false hope: How an obscure drug became a coronavirus 'cure' | The Fact Checker
Keywords: Hydroxychloroquine; chloroquine; coronavirus; incorrect cure